HUBUNGAN ANTARA TANGGUNG JAWAB DAN KOMITMEN DENGAN KEPEMIMPINAN LINGKUNGAN DALAM PENERAPAN PEMBANGUNAN BERKELANJUTAN - Sukiman Jayanto; Muhammad Zid; Yusriani Sapta Dewi (Program Studi Manajemen Lingkungan, 2018)
Abstract This study aims to determine whether there is a relationship between responsibility and commitment with environmental leadership in sustainable development of correlational studies in West Sumbawa, NTB. The correlational method used by sampling 130 people in the employee in West Sumbawa Regency, NTB as a sample selected by multy stages random sampling. Environmental leadership in the implementation of sustainable development after the validity test then obtained 28 questions and 6 drop problems with reliability of 0.912. Test the validity of responsibilities (x1) of 27 valid issues that is 20 with reliability of 0.894. Test validity of commitment from 48 item valid matter that is valid 33 with reliability equal to 0,961 Data have been analyzed by applying descriptive statistic and correlational test (R) to verify there is relation between variable. The results show that there is a relationship between responsibility and commitment with environmental leadership in sustainable development. Keywords: responsibility, commitmen, environmental leadership in the implementation of sustanable development